Assessment of Different Control Strategies for Precision Laser Alignment and Distance Estimation - Fredriksson, Philip; Nordemark, Alexander (My University, 2025)
This thesis investigates and evaluates different control strategies for automating the alignment of laser beams in high-precision measurement systems, specifically within Easy-Laser’s XT20 platform. The aim is to replace the manual adjustment process with an automated system capable of aligning a laser beam with a Position Sensitive Device (PSD) and estimating the relative distance between the transmitter and detector. A comprehensive system model incorporating a brushed DC motor and its mechanical interface is developed. Both physical modeling and system identification techniques are employed, followed by the design and implementation of two control algorithms: cascade PID and Linear Quadratic Integrator (LQI). The control strategies are compared in terms of response time, overshoot, steady-state error, and robustness. To improve real-world performance, the controllers are further enhanced with signal filtering and a feedforward friction compensator. Experimental results demonstrate that the LQI controller with feedforward compensation performs best, achieving sub-2 second alignment times. The thesis also explores methods for detector localization and distance estimation using the PSD; however, full localization was not achieved. The final solution significantly improves measurement speed and alignment accuracy, enabling automated laser beam positioning within 30 seconds—matching the performance of a skilled human operator, while highlighting key areas for future development.